Dynamics of the Mudarabah Agreement: Optimization Models and Strategies in the Islamic Banking System - Zainol Huda (Universitas Muhammadiyah Palu, 2022)
Akad mudarabah is one of the financial products that is often used in Islamic banking, where the bank acts as the owner of capital (rabb al-maal) and the customer as the business manager (mudarib). Most of the research tends to focus on certain models of the mudarabah contract without developing a more comprehensive and adaptive model to market dynamics and Islamic banking regulations. There is a need for the development of more holistic models that can be flexibly implemented in a variety of conditions. This research will not only enrich the academic literature on the Mudarabah contract, but also make a practical contribution to the Islamic banking industry, especially in terms of optimizing these financial products to achieve broader Islamic economic goals